The promise not to sue in the interpretation of the Superior Court of Justice versus its possibility (Research, Society and Development, 2022)
The research refers to the atypical legal business of the promise not to sue (pacto de non petendo) covered by its possibility by the provisions of art. 190 of the Civil Procedure Code. Despite rare Brazilian doctrine explaining the subject, the Fourth Panel of the Superior Court of Justice, in the rapporteurship of Minister Luis Felipe Salomão in Special Appeal 1,810,444-SP, established the thesis of invalidity of the non petendo pact clause due to of its suppression to the adversary system and to the constitutional guarantee of judicial protection (article 5, items LV and XXXV, Federal Constitution of 1988), therefore, object of public order and contrary to the constitutional provision, and cannot be agreed between the parties. However, the discussion on the subject is still necessary, since its possible applicability within the dictates of private autonomy is understood. The objective is, therefore, to carry out a counterpoint between the vote rendered and the doctrine that focused on the clause of not prosecuting. Through the deductive and dialectical methodology, a doctrinal and jurisprudential study is presented.